Alumina-toughened zirconia nanocomposite: Aging effect on microstructural, optical, and mechanical properties - Piza, Mariana M.T.; Bergamo, Edmara T.P.; Campos, Tiago M.B.; Carvalho, Laura F.; Goulart, Celso A. [UNESP]; Gutierres, Eliezer; Lopes, Adolfo C.O.; Benalcazar Jalkh, Ernesto B.; Bonfante, Estevam A. (Elsevier, 2023)
Objectives: To process an alumina-toughened zirconia (ATZ) nanocomposite and to characterize its crystalline phases, microstructure, residual stress, mechanical and optical properties before and after two different artificial aging methodologies. Methods: Disc-shaped specimens were obtained through uniaxial pressing of a commercial ATZ powder comprised of 80%ZrO2 / 20%Al2O3, with a particle size of 50 nm and 150 nm, respectively. Sintering was performed at 1500ºC for 2 h. Groups were established according to the aging protocol as immediate (ATZ-I) and aged either in autoclave (ATZ-A) or hydrothermal reactor (ATZ-R) at 134 ºC for 20 h at 2.2 bar. Crystalline phases and microstructure were assessed by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. Residual stress was evaluated by Raman spectroscopy. Contrast Ratio (CR) and Translucency Parameter (TP) were calculated to characterize optical properties. Mechanical properties were analyzed through Vickers microhardness, fracture toughness, and biaxial flexural strength test. Results: XRD spectra of both aging protocols revealed the presence of monoclinic zirconia (20–31%), where higher phase transformation was observed after aging in hydrothermal reactor. Optical properties evaluation demonstrated high opacity (CR: 0.99) and masking ability (TP: 0.26), with no significant differences after aging. Raman spectroscopy evidenced the presence of residual compressive stresses in the aged groups, being significantly higher for ATZ-R (−215.2 MPa). As-sintered specimens revealed hardness of ∼12.3 GPa and fracture toughness of ∼1.9 MPa.m1/2. Characteristic strength was 740 MPa for ATZ-I, 804 MPa for ATZ-A, and 879 MPa for ATZ-R, with significant differences between groups. Weibull modulus ranged from 16.5 to 18.8. All groups demonstrated high reliability up to 500 MPa stress missions (99–100%), with no significant differences after aging. Significance: The experimental ATZ nanocomposite presented high opacity and a high Weibull modulus. While aging created internal compressive stress responsible for an increase in characteristic strength, the nanocomposite was susceptible to hydrothermal degradation. Further studies are required to evaluate its degradation kinetics at low temperatures.
Keywords: Aging; Ceramic Composites; Mechanical properties; Zirconia